Body image and weight management: young people, internet advertisements and pharmacists - Luevorasirikul, Kanokrat (2007)
Media promotion of the ideal body as slimness for women and muscularity for men, has led to increasing numbers of both genders reporting dissatisfaction with their bodies and trying to change using weight control products. It has been suggested that pharmacists can play a key role in promoting healthy lifestyles and weight management.